Pushing the Limits in Cheek Reconstruction: The Sub-Superficial Musculo-Aponeurotic System "Deep Plane" Cervicofacial Flap for Reconstruction of Large Eyelid-Cheek Junction Defects. Issue 7 (October 2020) - Purnell, Chad A.; Bricker, Jonathan T.; Alghoul, Mohammed S.
Abstract : Abstract: The cervicofacial flap is a workhorse flap for reconstruction of moderate to large sized defects of the cheek. Defects that involve the eyelid-cheek junction are often the most challenging of these. While the ideal plane of dissection has been debated, it is our belief that dissection in the sub-superficial musculo-aponeurotic system (SMAS) plane provides better aesthetic and functional outcomes due to enhanced vascularity, fascial support, and additional bulk of the flap itself. The authors present a series of 9 patients who presented with heterogeneous defects of the eyelid-cheek junction after cancer resection and underwent reconstruction using a sub-SMAS cervicofacial flap. At a mean follow-up time of 20 months, the cohort had 2 patients who developed lower lid retraction requiring revision and 2 other minor complications. This series lends support to the versatility and reliability of the sub-SMAS cervicofacial flap for large defects of the eyelid-cheek junction. Abstract : Supplemental Digital Content is available in the text